Allelopathic potential of marshpepper residues for weed management and yield of transplant Aman rice - Pramanik, SK; Uddin, MR; Sarker, UK; Sarkar, D; Ahmed, F; Alam, MJ (Progressive Agriculture, 2020)
An experiment was conducted at the Agronomy Field Laboratory, Bangladesh Agricultural University, Mymensingh, during the period from June to December 2016 to evaluate the effect of marshpepper (Polygonum hydropiper L.) crop residues on weed management and crop performance of transplant aman rice. The experiment consisted of three cultivars viz. BR11, BRRI dhan33 and BRRI dhan49 and five marshpepper crop residues treatment such as 0, 1.0, 2.0, 3.0 ton ha-1 and hand weeding. The experiment was laid out in a randomized complete block design (RCBD) with three replications. Five weed species belonging to four families infested the experimental plots. Weed population and weed dry weight were significantly affected by cultivar and crop residues treatment. The highest percent inhibition of all the studied weed was found by hand weeding. The second highest percent weed inhibition was found with the application of marshpepper residues at 3.0 t ha-1 which was 63.43, 63.43, 52.85, 52.40 and 59.12 percent for sabuj nakful (Cyperus difformis), chesra (Scirpus juncoides), shama (Echinochloa crusgalli) panikachu (Monochoria vaginalis) and panishapla (Nymphaea nouchali ) respectively. The maximum weed growth was noticed with the cultivar BRRI dhan33 variety and the minimum was found in the cultivar BRRI dhan49. The grain yield as well as the yield contributing characters produced by BRRI dhan49 was the highest among the studied varieties. The highest reduction of grain yield was obtained in no crop residue treatment. The highest number of effective tillers hill-1, number of grains panicle-1, 1000-grain weight, grain and straw yields were observed in marshpepper residues in hand weeding followed by 3.0 t ha-1 marshpepper crop residue. BRRI dhan49 produced the highest grain and straw yields under hand weeding followed by marshpepper residues 3.0 t ha-1 treatment. Results of this study indicate that marshpepper residues showed potentiality to inhibit weed growth and it has a significant effect on the yield of transplant aman rice. Therefore, marshpepper residues might be used as an alternative way for weed management effective and sustainable crop production. Progressive Agriculture 30 (4): 379-386, 2019